GEOLOCATION: LOCATING TRUST IN DIGITAL PLATFORMS AND ECONOMIES - Mitchell, Peta; Leszczynski, Agnieszka; Zook, Matthew; Blankenship, Joe; McGrane, Caitlin; Hjorth, Larissa; Thomas, Julian; Wilken, Rowan (AoIR Selected Papers of Internet Research, 2019)
Digital location—or geolocation—is a fixture of digital platforms and economies, figuring as an organizational logic for content and user experience (e.g., map-based interfaces), native technical affordance (e.g., locational functionalities of GPS-enabled smartphones), and core enabling agent behind the rise of ‘disruptive’ platform enterprises (e.g., Uber, Deliveroo, and Waze all rely on geolocation for service delivery). Despite its inextricability from contemporary media, data productions, and digital practices, geolocation’s role in fostering mis/trust in digital systems has to date been unaddressed. The papers in this panel identify and theorize the ways in which geolocation functions as simultaneously a key ‘technology of trust’ (sociotechnical agent through which mis/trust is bred and/or secured in digital ecosystems), and a social relation of trustworthiness in digital platforms and economies, exploring the role geolocation plays form the perspectives of both securing trust and breeding mistrust in digital systems.